Scandinavian Management as the Recipe for Health - Stańczyk, Sylwia (Zarządzanie skandynawskie jako recepta na rozwój, 2010)
For some time the Scandinavian style of management has become an idee fixe for international management specialists. The purpose of this paper is to conduct a cultural analysis of the Scandinavian model of management from the theoretical, scientific and economic point of view. The article assumes that the culture of a country exerts certain influence on the preferred management style. These issues are crucial for the understanding of international management.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 148, s. 226-236
Keywords: Scandinavian management; Scandinavian culture; international management